Promoting Critical Thinking through an SDG-Integrated STEAM E-Module for Grade X High School Students - Pauzi; Rayendra; Abna Hidayati; Ulfia Rahmi (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to produce STEAM-based E-Modules that are valid, practical, and effective in improving students' critical thinking skills in mathematics subjects. This research uses the ADDIE development model with five steps: Analysis, Design, Development, Implementation, and Evaluation. The validity of the E-Module was tested by four validators, namely experts in instruments, media, materials, and languages. Trial I involved 3 students, while trial II was carried out on 2 educators and 25 students. The results showed that the STEAM-based E-Module on linear program materials had excellent validity, with a score of 83% for product experts, 93% for subject matter experts, and 93% for linguists. The practicality of this E-Module is very high, with the trial of students obtaining a score of 98% and educators 96%, both of which are in the category of "Very Practical". The effectiveness of this E-Module can be seen from the increase in student learning outcomes, namely from a pretest score of 49.60 to a posttest score of 81.40, with an N-gain of 0.62 which is included in the "Medium" category. In addition, students' critical thinking abilities earned an average score of 3.03 out of 4, which indicates the "Pretty Good" category. The results of this study show that STEAM-based E-Modules are effective in improving students' critical thinking skills and are practically used in mathematics learning.